CARACTÉRISATION PHYSICO CHIMIQUE ET TECHNOLOGIQUE DES VARIÉTÉS DE MIL PENNISETUM GLAUCUM (L.) R. BR.) OUEST AFRICAINES - Békoye, Béninga Marboua (European Scientific Journal, ESJ, 2014)
Fifteen (15) west African pearl millet varieties comprising eight (8) from Senegal and seven (7) from Côte d’Ivoire were characterized for their physico-chemical and technological qualities. Thousand grains weight ranged from 5.98 g to 9.94 g; Mean and standard deviation values for this parameter were respectively 8.03 g and 0.18. Five Côte d’Ivoire varieties and three from Senegal are above this mean value. They are SRR2, VPCN, VPNW, VPNE and LOCAL FERKE for Côte d’Ivoire and for Senegal : ISMI 9102, ISMI 9301 and ISMI 9303. Having the highest 1000 grains weight, they consequently will present better outputs potential millers. The contents of proteins ranged from 8.31 % to 12.01 % for all the varieties with 10.52 % mean value. All Senegalese varieties are above the mean value while only one Côte d’Ivoire variety (VPP) is above. Fat content in the grains values ranged from 4.75 % to 5.90 % and the mean value is 5. 14. Five varieties from Senegal and three from Côte d’Ivoire are superior to the mean. The best varieties for fat contents were ISMI 9102, ISMI 9303, ISMI 9305 and SOUNA 3 for Senegal then SRR2, VPNE and LOCAL FERKE for Côte d’Ivoire. The phosphorus contents mean value is 0.30 for the fifteen varieties. Five Senegalese varieties and three Côte d’Ivoire varieties are above this mean value. Results of technological analysis showed that when particle size index (PSI) and abrasive hardness index (AHI) were combined, varieties SRR1, VPCN, VPP and SRR2 from Côte d’Ivoire and varieties ISMI 9203, ISMI 9304, ISMI 9102 and SOUNA 3 from Senegal present good aptitude to decortication.